Beyond profession : the next future of theological education - Aleshire, Daniel O., 1947- (Grand Rapids, Michigan : : William. B. Eerdmans Publishing Company, 2021)
"A reflection on the historical evolution of American theological education and its possible future development focused on formation"--
Includes bibliographical references.
Keywords: Theology -- Study and teaching -- United States -- History